2016
DOI: 10.1039/c6cc05360b
|View full text |Cite
|
Sign up to set email alerts
|

Lewis acid catalysis: catalytic hydroboration of alkynes initiated by Piers' borane

Abstract: Terminal and internal alkynes are efficiently hydroborated to (E)-alkenyl pinacol boronic esters with excellent yields and selectivities using a Lewis acid catalyst. In the case of Piers' borane (HB(C6F5)2) the borane acts as a pre-catalyst generating dissymmetrically gem-diborylated species of the form RCH2CR'(Bpin)(B(C6F5)2) which are the active catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(52 citation statements)
references
References 43 publications
2
50
0
Order By: Relevance
“…Interestingly, 1,1-bis(boryl)alkanes can behave as catalysts, too. Piers's borane V [HB(C 6 H 5 ) 2 ] precatalyzed the hydroboration of terminal and internal alkynes for the synthesis of E-alkenyl pinacol boronic ester 36, and excellent selectivities were reported by Stephan and coworkers in 2016 [34]. In this hydroboration, they found that unsymmetrical 1,1-bis(borane) 34 catalyzed the reaction.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…Interestingly, 1,1-bis(boryl)alkanes can behave as catalysts, too. Piers's borane V [HB(C 6 H 5 ) 2 ] precatalyzed the hydroboration of terminal and internal alkynes for the synthesis of E-alkenyl pinacol boronic ester 36, and excellent selectivities were reported by Stephan and coworkers in 2016 [34]. In this hydroboration, they found that unsymmetrical 1,1-bis(borane) 34 catalyzed the reaction.…”
Section: Methodsmentioning
confidence: 96%
“…The proposed mechanism for the unsymmetrical 1,1-bis(borane) 34 catalyzing the hydroboration of alkynes for the synthesis of E-alkenyl boronic ester 36 is shown in Scheme 10. In this mechanism, unsymmetrical 1,1-bisboranes 34 acts as a Lewis acid catalyst, which activates alkyne to form complex VI: then, HBpin reacts with complex VI in a concerted syn-1,2-hydroboration manner (complex VII) to afford the hydroborylated product 36 and regenerate the unsymmetrical 1,1-bis(borane) 34 [34].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Later,K nochel reported as imilar hydroboration of alkynes at room temperature with two equivalents of pinacolb orane,w hich is nowadays the most popularb oronate reagent owing to its great stability in air or during chromatography purifications (Scheme 1b). [8] Dicyclohexylborane [9] or HB(C 6 F 5 ) 2 [10] have been reported as catalysts for this reaction.…”
Section: Synthesis Of E-alkenyl Boronatesmentioning
confidence: 99%
“…[13,14] Similar reactivity has also been observed with substituted perfluoroaryl borane HB(C 6 F 5 ) 2 . [15] Herein, we discuss the synthesis of an arsanyl-phosphaketene which,u pon reactionw ith B(C 6 F 5 ) 3 ,w as found to yield an arsaphosphene in ar are cis-configuration. Moreover,w hen catalytic amounts of B(C 6 F 5 ) 3 were used, we found that dimeric species are generated through af ormal [2+ +2] cycloadditiono f the cyclic arsaphosphene.…”
mentioning
confidence: 99%